Metabolic profiling of a myalgic encephalomyelitis/chronic fatigue syndrome discovery cohort reveals disturbances in fatty acid and lipid metabolism - Germain, Arnaud (Mol Biosyst, 2017)
Myalgic Encephalomyelitis/Chronic Fatigue Syndrome (ME/CFS) remains a continuum spectrum disease without biomarkers or simple objective tests, and therefore relies on a diagnosis from a set of symptoms to link the assortment of brain and body disorders to ME/CFS. Although recent studies show various affected pathways, the underlying basis of ME/CFS has yet to be established. In this pilot study, we compare plasma metabolic signatures in a discovery cohort, 17 patients and 15 matched controls, and explore potential metabolic perturbations as the aftermath of the complex interactions between genes, transcripts and proteins. This approach to examine the complex array of symptoms and underlying foundation of ME/CFS revealed 74 differentially accumulating metabolites, out of 361 (P<0.05), and 35 significantly altered after statistical correction (Q<0.15). The latter list includes several essential energy-related compounds which could theoretically be linked to the general lack of energy observed in ME/CFS patients. Pathway analysis points to a few pathways with high impact and therefore potential disturbances in patients, mainly taurine metabolism and glycerophospholipid metabolism, combined with primary bile acid metabolism, as well as glyoxylate and dicarboxylate metabolism and a few other pathways, all involved broadly in fatty acid metabolism. Purines, including ADP and ATP, pyrimidines and several amino acid metabolic pathways were found to be significantly disturbed. Finally, glucose and oxaloacetate were two main metabolites affected that have a major effect on sugar and energy levels. Our work provides a prospective path for diagnosis and understanding of the underlying mechanisms of ME/CFS.